Market Orientation Model in Indonesia Special Autonomy Regional Government - Ahmad Hudalil (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study aimed to inspect the effect of information technology infrastructure on market orientation. It also intended to examine the impact of market orientation on organizational achievement in Special Autonomy Regional Government. Research methodology: The study adopted a quantitative research design and obtained samples using cluster and stratified random sampling. The samples were determined on the Gross Regional Domestic Product (GRDP) size of Indonesia's five Special Autonomy Regional Governments. Questionnaire items were distributed to the targeted sample from two clusters of Jakarta Special Capital Province and West Papua Province. The two provinces have the highest and lowest GRDP, respectively. Data were collected from 210 respondents comprising the deputy employers in the regional work units of West Papua Province and Jakarta Special Capital. The data were analyzed using Structural equation modeling (SEM) partial least square (PLS) with LISREL 8.80. Results: The results showed that information technology infrastructure affects market orientation, which mediates the impact of organizational performance of Indonesia's Special Autonomy Regional Government.